Outcomes of unilateral and bilateral total knee arthroplasty in 238, 373 patients. (15th June 2016) - Bohm, Eric R; Molodianovitsh, Katy; Dragan, Alina; Zhu, Naisu; Webster, Greg; Masri, Bas; Schemitsch, Emil; Dunbar, Michael
Abstract : Background and purpose — There is no consensus about the outcome of simultaneous vs. staged bilateral total knee arthroplasty (TKA). We examined this issue by analyzing 238, 373 patients. Patients and methods — Demographic, clinical, and outcome data were evaluated for TKA patients (unilateral: 206, 771; simultaneous bilateral: 6, 349; staged bilateral: 25, 253) from the Canadian Hospital Morbidity Database for fiscal years 2006–2007 to 2012–2013. Outcomes were adjusted for age, sex, comorbidities, and hospital TKA volume. Results — Simultaneous bilateral TKA patients were younger than staged bilateral TKA patients (median 64 years vs. 66 years), were more likely to be male (41% vs. 39%), and had a lower frequency of having ≥1 comorbid condition (2.9% vs. 4.2%). They also had a higher frequency of blood transfusions (41% vs. 19%), a shorter median length of stay (6 days vs. 8 days), a higher frequency of transfer to a rehabilitation facility (46% vs. 9%), and a lower frequency of knee infection (0.5% vs. 0.9%) than staged bilateral TKA patients, but they had higher rate of cardiac complications within 90 days (2.0% vs. 1.7%). Simultaneous patients had higher in-hospital mortality compared to the second TKA in staged patients (0.16% vs. 0.06%), but they had similar rates of in-hospital mortality compared to unilateral patients (0.16% vs. 0.14%). The cumulative 3-year revision rate was highest in the unilateral group (2.3%), but it was similar in the staged and simultaneous bilateral groups (1.4%). Interpretation — We found important differences between the outcomes of simultaneous and staged bilateral TKA. Further clarification of outcomes would be best determined in an adequately powered randomized trial, which would remove the selection bias inherent in this retrospective study design.